Navzočnost v času - Krevel, Mojca (Primerjalna književnost, 2016)
Analysing the concepts of subject and reality in Ruth Ozeki's A Tale for the Time Being from the perspective of the governing principles of postmodern societies and cultures, the article charts the effects of current social and historical conditions, as well as the change of the dominant medium on novel and literature in general.
Keywords: American literature; ameriška književnost; Ozeki, Ruth: A Tale for the Time Being; ameriški roman; čas; postmoderna; reality; resničnost; hiperresničnost; hipertekst; hypertext; fraktalni subjekt